The Formula: How Rogues, Geniuses, and Speed Freaks Reengineered F1 Into the World's Fastest-Growing Sport : How Rogues, Geniuses, and Speed Freaks Reengineered F1 Into the World's Fastest-Growing Sport - Robinson, Joshua, 1986-; Clegg, Jonathan, 1980- (New York : Mariner Books, 2024)
"WALL STREET JOURNAL reporters and authors of THE CLUB, Joshua Robinson and Jonathan Clegg tell the riveting saga of how Formula 1 broke through in America, detailing the eclectic culture of racing obsessives, glamorous settings, gearheads, engineering geniuses, dashing racers, and bitter rivalries that have made F1 the world's fastest growing sport. For decades in America, car racing meant NASCAR, and to a lesser extent IndyCar, with Formula 1-the wealthiest racing league in the world-a distant third. Fast forward to 2023, and F1 has emerged at the front of the pack powered by a passionate yet nascent American fanbase. The F1 juggernaut has arrived, but this checkered flag was far from inevitable. In THE FORMULA, WALL STREET JOURNAL reporters Joshua Robinson and Jonathan Clegg tell the epic story of how F1 saved itself from collapse and finally conquered America through guile, fearlessness, and above all, reinvention. With fast cars, big money, glamorous locales, and beautiful people as the backdrop, THE FORMULA reveals how F1's sudden arrival in the US was actually decades in the making, a product of the sport's near-constant state of transformation and experimentation. Bringing unique insight and access to F1's most storied teams and personalities-from Ferrari to Bernie Ecclestone to Christian Horner to Lewis Hamilton-THE FORMULA offers a riveting portrait of the drivers, corporations, cars, rivalries, and audacious gambles that have shaped the sport for half a century. The end result is a high-octane history of how modern F1 racing came to be-the first book to tell the story of the outrageous successes and spectacular crashes that led F1 to this extraordinary yet precarious moment. More than just a sports story, THE FORMULA is the tale of a disrupter that broke into the crowded American sports marketplace and claimed its place through cash, personality, and a new understanding of what a sport needs to be in the age of wall-to-wall entertainment"--.
new book 2024 fall.
Includes bibliographical references (pages 281-282) and index.
Keywords: Grand Prix racing -- History; Formula One automobiles -- History